Studi Kelayakan Bisnis Pengembangan Usaha Pada UMKM Friskia Ala Ala Wedding Organizer - Susilawati Susilawati; Sehwuda Sehwuda; Siti Maryam H; Tasha Ratna Dewi; Wiwin Fadila; Yani Nuryani (Jurnal Akuntan Publik, 2025)
A wedding is a very important moment for everyone and requires meticulous preparation, sometimes taking months to years, but the lack of time and support from friends and family is often not enough to fulfill all the needs for planning a wedding. In this case, wedding organizers (WOs) are here to solve this problem. This study aims to examine the development of a growing wedding designing business in Tanjungwangi Village, Pacet, Bandung Regency, especially Friskia Ala Ala Wedding Organizer. This research provides an in-depth description of client experiences, processes, and variables that contribute to the services they offer. The method used in this research is, descriptive qualitative method with the technique of collecting data through direct observation and interviews. Friskia Ala Ala Wedding Organizer offers various services, such as make-up artist (MUA), prewedding, decoration, location, catering, photography, film, and entertainment. Friskia Ala Ala Wedding Organizer conducted a SWOT analysis which showed that there are strengths to attract customers and low prices. Friskia Ala Ala Wedding Organizer managed to record a good profit from the sale of its wedding packages. In addition, the net profit generated shows good financial management. The conclusion of this study highlights the development of business feasibility, marketing strategy, service production process, as well as management